Exploring the strategies and benefits of integrating fashion brands with tourism by analyzing the Valentino Pink PP campaign in Anaya - Yan, Jiaqi (Transactions on Economics, Business and Management Research, 2024)
Using Valentino's “Pink PP” campaign in Anaya as a starting point, this study explores the strategies and benefits of integrating tourism and fashion brands. Through a comprehensive analysis of social media data, tourism statistics, and brand marketing reports, this study finds that brand linkage strategies can effectively increase brand awareness and destination attractiveness, social media communication and word-of-mouth effects play an important role in promoting brand development and tourism prosperity, and immersive experiences can enhance the emotional connection between consumers and brands and promote synergistic development between brands and tourism. Based on the above findings, this study puts forward three recommendations: fashion brands should fully explore their brand influence and enhance their market competitiveness through cooperation with the tourism industry; they should implement innovative marketing strategies by grasping the social media communication and word-of-mouth effects; and they should focus on the emotional resonance with consumers and consumer experience-centered marketing strategies, so as to realize the sustainable development of the brand and the enhancement of its market competitiveness.